Screening and brief interventions for hazardous and harmful alcohol use in primary care: a cluster randomised controlled trial protocol - Newbury-Birch Dorothy; Myles Judy; Heather Nick; Godfrey Christine; Gilvarry Eilish; Drummond Colin; Deluca Paolo; Coulton Simon; Cassidy Paul; Bland Martin; Kaner Eileen; Oyefeso Adenekan; et al. (BMC, 2009)
Abstract Background There have been many randomized controlled trials of screening and brief alcohol intervention in primary care. Most trials have reported positive effects of brief intervention, in terms of reduced alcohol consumption in excessive drinkers. Despite this considerable evidence-base, key questions remain unanswered including: the applicability of the evidence to routine practice; the most efficient strategy for screening patients; and the required intensity of brief intervention in primary care. This pragmatic factorial trial, with cluster randomization of practices, will evaluate the effectiveness and cost-effectiveness of different models of screening to identify hazardous and harmful drinkers in primary care and different intensities of brief intervention to reduce excessive drinking in primary care patients. Methods and design GPs and nurses from 24 practices across the North East (n = 12), London and South East (n = 12) of England will be recruited. Practices will be randomly allocated to one of three intervention conditions: a leaflet-only control group (n = 8); brief structured advice (n = 8); and brief lifestyle counselling (n = 8). To test the relative effectiveness of different screening methods all practices will also be randomised to either a universal or targeted screening approach and to use either a modified single item (M-SASQ) or FAST screening tool. Screening randomisation will incorporate stratification by geographical area and intervention condition. During the intervention stage of the trial, practices in each of the three arms will recruit at least 31 hazardous or harmful drinkers who will receive a short baseline assessment followed by brief intervention. Thus there will be a minimum of 744 patients recruited into the trial. Discussion The trial will evaluate the impact of screening and brief alcohol intervention in routine practice; thus its findings will be highly relevant to clinicians working in primary care in the UK. There will be an intention to treat analysis of study outcomes at 6 and 12 months after intervention. Analyses will include patient measures (screening result, weekly alcohol consumption, alcohol-related problems, public service use and quality of life) and implementation measures from practice staff (the acceptability and feasibility of different models of brief intervention.) We will also examine organisational factors associated with successful implementation. Trial registration Current Controlled Trials ISRCTN06145674.